Melatonin Potentiates Exercise-Induced Increases in Skeletal Muscle PGC-1α and Optimizes Glycogen Replenishment - Faria, Vinícius Silva; Manchado-Gobatto, Fúlvia Barros; Scariot, Pedro Paulo Menezes; Zagatto, Alessandro Moura; Beck, Wladimir Rafael (Frontiers in Physiology, 2022)
Compelling evidence has demonstrated the effect of melatonin on exhaustive exercise tolerance and its modulatory role in muscle energy substrates at the end of exercise. In line with this, PGC-1α and NRF-1 also seem to act on physical exercise tolerance and metabolic recovery after exercise. However, the literature still lacks reports on these proteins after exercise until exhaustion for animals treated with melatonin. Thus, the aim of the current study was to determine the effects of acute melatonin administration on muscle PGC-1α and NRF-1, and its modulatory role in glycogen and triglyceride contents in rats subjected to exhaustive swimming exercise at an intensity corresponding to the anaerobic lactacidemic threshold (iLAn). Thirty-nine Wistar rats were allocated into four groups: control (CG), rats treated with melatonin (MG), rats submitted to exercise (EG), and rats treated with melatonin and submitted to exercise (MEXG). Forty-eight hours after the graded exercise test, the animals received melatonin (10 mg/kg) or vehicles 30 minutes prior to time to exhaustion test in the iLAn (tlim). Three hours after tlim the animals were euthanized, followed by muscle collection for specific analyses: soleus muscles for immunofluorescence, gluteus maximus, red and white gastrocnemius for the assessment of glycogen and triglyceride contents, and liver for the measurement of glycogen content. Student t-test for independent samples, two-way ANOVA, and Newman keuls post hoc test were used. MEXG swam 120.3% more than animals treated with vehicle (EXG; p < 0.01). PGC-1α and NRF-1 were higher in MEXG with respect to the CG (p < 0.05); however, only PGC-1α was higher for MEXG when compared to EXG. Melatonin reduced the triglyceride content in gluteus maximus, red and white gastrocnemius (F = 6.66, F = 4.51, and F = 6.02, p < 0.05). The glycogen content in red gastrocnemius was higher in MEXG than in CG (p = 0.01), but not in EXG (p > 0.05). In conclusion, melatonin was found to enhance exercise tolerance, potentiate exercise-mediated increases in PGC-1α, decrease muscle triglyceride content and increase muscle glycogen 3 hours after exhaustive exercise, rapidly providing a better cellular metabolic environment for future efforts.